Russia’s Foreign Policy Ideologemes and Their Relevance for Middle East in Context of Transformation of Modern System of International Relations - Vladimir A. Avatkov; Danila S. Krylov (RUDN Journal of Political Science, 2023)
As part of this research, there was made an analysis of the foreign policy ideas, values and narratives of the Russian Federation distributed in the information sphere based on the theses that were voiced by the President of Russia V. Putin during his speeches in 2022. These ideas were considered through the prism of ideologemes that determine the strategic vector foreign policy of official Moscow. In addition, an assessment is made of the relevance of these ideologemes for the states of the Middle East region in the context of changes in the global transformation of the entire system of international relations and the building of a new polycentric world order. Conclusions are drawn about the interest of the cross-regional actors of the Middle East subsystem in the promotion of the theses and ideologies put forward by Russia and a certain identity and coincidence of the ideological and value spaces of Russia and the countries of the Middle East. Aspects and directions are outlined in which cooperation and coordination of actions between Moscow and the Middle East leaders can develop. An assumption is put forward about the possibility of building a system of rules and ideas in the Middle East, which can subsequently be extrapolated to the entire global system of international relations.